The contribution of the BIOTA/FAPESP Program to the advancement of the knowledge on terrestrial invertebrates - Noll, Fernando B. [UNESP] (2022)
The variability of the organisms living in a given area constitute what is referred to as biodiversity, one of nature’s fundamental properties, responsible for the balance and stability of ecosystems. The loss of biodiversity has been of great concern to scientists, especially because of the role played by human activities in this regard, able to lead to irreversible circumstances. The São Paulo Research Foundation (Fundação de Amparo à Pesquisa do Estado de São Paulo, FAPESP) plays a major role in supporting research efforts in the most diverse branches of science. In the late 1990´s, FAPESP launched a major program to promote research on biodiversity, named BIOTA/ FAPESP. So far, this program has financed the conduction of 26 projects, involving research activities in most of Brazil, while focusing mainly the State of São Paulo. These projects have generated about 1140 publications in peer-reviewed journals of high standard, providing relevant information, including the original description of 1187 species and 76 genera, the complementary description of 350 species, as well as a number of inventory works, biological studies, etc. The program has also been instrumental in the establishment or adequacy of research facilities and training of new taxonomists. Most extensively studied groups of terrestrial invertebrates include Insecta of the orders Hymenoptera, Lepidoptera and Diptera, and Arachnida of the subclasses Araneae and Acari. Distinct projects have also contributed to the detection of organisms potentially useful as biological control agents and in the determination of maps of major interest for the establishment of public policies. In the future, priority groups for study should include the Annelida and the Nematoda, for the potential both have as beneficial organisms, or for the potential some Nematoda have as organisms harmful to plants and animals.